Raman characterization of single-walled nanotubes of various diameters obtained by catalytic disproportionation of CO - Herrera, Jose E. (2003)
Single-walled carbon nanotubes prepared by disproportionation of CO over Co-Mo/SiO 2 catalysts have been characterized by Raman spectroscopy, using several excitation energies. By varying the reaction temperature, different ranges of nanotube diameter were obtained. The average diameter of a single-walled nanotube produced at 750°C was 0.9 nm, while it increased up to about 1.5 nm when the synthesis was conducted at 950°C. The analysis of the Raman spectra obtained with a range of laser excitation energies not only gives a definite description of the single-walled nanotubes diameters but also helps differentiate the metallic or semiconducting character of the samples. This analysis can be done by comparing the experimental data with calculated gap energies as a function of nanotube diameter as well as comparing the relative intensity of bands centered at 50-60 cm -1 lower than the tangential G mode. The analysis of this feature, which can be fitted with a Breit-Wigner-Fano line, offers a method for distinguishing between metallic and semiconducting single-walled carbon nanotubes.